Simulation-based optimization for generating the dimensions of a dredged coastal entrance channel. (September 2014) - Tang, Guolei; Wang, Wenyuan; Guo, Zijian; Yu, Xuhui; Wang, Bingchang
An entrance channel is dredged when its natural dimensions are not adequate to accumulate more and larger ships. Considering the reconciliation among costs, safety and efficiency and the complex relationship among channel type, navigable water level and sailing speed, a simulation-based optimization framework is proposed to optimize channel dimensions with limited dredging budget constraints in an integrated way. In this framework, the optimization program generates channel dimensions acceptable for safe navigation with budget constraints, and seeks an optimal balance between the dredging costs and navigation efficiency, including vessel waiting time and berth utilization. The simulation model evaluates the values of navigation efficiency measures considering the randomness and dynamics in ship operation. Finally, an application is given and the results show that the proposed framework is effective and helpful for optimizing the dimensions of the entrance channel. Moreover, the proposed modeling and solution methods are general and can be applied to the port basin, anchorage area as well.